Work models to learn to entrepreneur in journalism - Peinado-Miguel, Fernando; Rodriguez-Barba, Dolores (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objective is to recognize a methodology to reinforce the transversality and globalization of applicable academic experiences in the Faculty of Journalism of the UCM. Work has been done on the Journalistic company subjects of the Degree in Journalism based on "Learning to undertake", through soft derived from the Learning Pyramid that provides students with sufficient qualities to undertake in communication. The results reinforce the need for an entrepreneurship center that facilitates monitoring of the best communication projects to guide them towards launchers such as Compluemprende.